6 The role of ablation index on repeat pulmonary vein isolation procedures in persistent atrial fibrillation: a short term outcome. (30th September 2020) - Lennon, SJ; Mannion, J; Szeplaki, G; Keaney, J; Keelan, E; Galvin, J; Boles, U
Abstract : Introduction: Ablation Index (AI) is a novel catheter-based parameter developed to improve and increase efficacy and safety of Pulmonary Vein Isolations (PVI) in the treatment of Atrial Fibrillation (AF). This method involves the incorporation of contact force, time and power in deliverance of ablation lines. The aim of this study is to evaluate the impact of AI on the AF free burden over one-year post redo ablation for persistent AF. The study evaluates a secondary endpoint in medical management escalations post procedure. Methods: A retrospective single centre study of 39 patients (Mater Private Hospital, Dublin) who had redo ablations for persistent AF between the period of Jan 2016 till December 2019. We evaluated and analysed the efficacy of AI on redo PVIs in comparison to conventional established ablation techniques. Both groups were matched for age, gender, and duration of PeAF. Group 1 (17 patients) was the AI group with ablation index intervention and group 2 was the contact force (CF) -guided group with 22 patients. Each cardiologist carried out a minimum of 100 ablations per year to confirm the uniformity of performance. Patient follow-up data was analysed at staged intervals for one-year post procedure. Inclusion criteria are: Patients must have had one prior PVI procedure for PeAF, complete follow up data available and all procedures completed using the Carto 3D Mapping System. Statistical analysis was carried out using SPSS (IBM SPSS Statistic Version 26). A Kaplan Meier graph was generated to evaluate the AF free interval. All continuous variables were expressed as the mean ± SD and Students T Test to was applied to give the significant differences for continuous variables. Results: Patient characteristics are demonstrated in Table 1 . There were no significant differences in age, sex, weight, height, CHADVASC or anti-arrythmia agents, which indicated similar patient profile in each cohort. Pulmonary vein reconnections at redo PVI procedure were comparable at 100% in the AI group and 86% in the CF group (p = 0.1). Freedom from AF burden was (mean 8.72 ± 4.33 months) in CF group Versus (mean 9.35 ± 4.1 months) in AI guided ablation (p=0.71) (figure 1 ). The AI group demonstrated greater numbers of patients in whom antiarrhythmic therapy could be deescalated over one year (AI, n=11/17, 65% Vs. CF, n=2/22, 9% with p=0.01) while fewer patients underwent escalation of their antiarrhythmic therapy (AI n=2/17, 12% vs CF n=6/22, 27% p= 0.03) (table 1 ). Conclusion: This is the first study to analyse the outcomes of ablation index on repeat PVI procedures. Despite no significant difference in AF recurrence outcomes demonstrated in this study, there was a significant difference in the medical de-escalation in favour of the use of the AI over the short term follow up period. This may reflect effective ablation lesions. A longer-term analysis would be recommended to determine the efficacy of AI use in PeAF redo procedures.